The value of the product expression (-2x-9y²)(-4x-3) is 8x² + 6x + 27y² + 36xy²
<h3>How to evaluate the product?</h3>
The expression is given as:
(-2x-9y²)(-4x-3)
Expand the expression
8x² + 6x + 27y² + 36xy²
Hence, the value of the product expression (-2x-9y²)(-4x-3) is 8x² + 6x + 27y² + 36xy²
Read more about products at:
brainly.com/question/10873737
#SPJ1
Let Cameron be x years old now.
-
<u>Now:</u>
Cameron = x
Uncle =3x
-
<u>4 years ago:</u>
Cameron = x - 4
Uncle = 3x - 4
-
<u>4 years ago, Uncle is 4 times older:</u>
3x - 4 = 4(x - 4)
-
<u>Find x:</u>
3x - 4 = 4(x - 4)
3x - 4 = 4x - 16
4x - 3x = 16 - 4
x = 12
-
<u>Find the age:</u>
Cameron = x = 12
-
Answer: Cameron is 12 years old now.
Answer:
10 ft cubed
Step-by-step explanation:
The volume of a pyramid is 1/3 the volume of a prism with the same base area & height.
30/3=10
It would be 3.5 as you start with 56 then take away 16 =40 then another witch is 24 the another 16 Is 8 so you have taken e16 away so far that's 3 pound and because you can take a full 16 off that makes it a half so final awnser is 3.5 56-16=40-16=24-16=8=3 pounds and a half hope I have helped you in any way
Yessssssssssssssssssssssss